The Use of Teaching Proficiency through Reading and Storytelling (TPRS) in Reading Skill - Afisah, Habsya (Journal of Education, Linguistics, Literature and Language Teaching, 2025)
This research aimed to find out how the use of Teaching Proficiency through Reading and Storytelling (TPRS) in students’ reading skill. The research was conducted in SMP Negeri 5 Langsa. A total of 20 students of class 9-1 were participated in this research. The data were collected using reading task and questionnaire. Then, the data collected were analyzed using experimental quantitative method. In collecting the data, the researcher gave students’ reading task which consists of pre-test and post-test. The result shows that the use of Teaching Proficiency through Reading and Storytelling improves students’ reading skill by enhancing students’ vocabulary acquisition through interesting stories. It is proved by the improvement of students’ reading score in post-test. The post-test shows higher score than in pre-test. Furthermore, the students perceive TPRS as a fun and enjoyable method to learn English. It motivates them to be more active in the class because the use of Personalized Questions Answers (PQA) and Personalized Mini Story (PMS). Moreover, the use of Teaching Proficiency through Reading and Storytelling enhances students’ motivation in the learning process by engaging students through interesting stories.